Angels of the Workplace : Women and the Construction of Gender Relations in the Canadian Clothing Industry, 1890-1940. - Steedman, Mercedes (Canadian social history series., 2009)
In this renowned 1997 study of the clothing industry in Canada, Mercedes Steedman examines how the intricate weaving together of the meanings of class, gender, ethnicity, family, and the workplace created a job ghetto for women.